PELIBATAN MASYARAKAT DALAM MERANCANG GERBANG MASUK DI DESA SETANGGOR - Jasmine Chanifah Uzdah Bachtiar; Ni Ketut Ayu Intan Putri Mentari Indriani; Rini Srikus Saptaningtyas; Liza Hani Saroya Wardi (Jurnal Abdi Insani, 2023)
Regional image-forming elements are needed to create a strong image to form branding of a region. These elements have been built in Setanggor Village, but the image you want to show and the impression of the village as a tourism destination is not visible. Village entrance gate designs are also designed with various shapes, designs and colors. This service was carried out as a forum for the community to voice their aspirations in developing the village through involvement in the design of the entrance gate to Setanggor Village. Community involvement was carried out through deliberation by presenting ideas and gate design concepts that had been created by the service team for village development. The results of the discussion showed that the Setanggor Village community agreed to the proposed third alternative (traditional concept) with several additions and changes in design. The addition of the Central Lombok Regency logo, the addition of the phrase 'cultural tourism village', and the beleq drum statue were carried out after the service activities were completed. The results of the third alternative design were sent back as discussion material for the Village Head and the community for budget planning. This service activity has a positive impact on residents because it can increase residents' knowledge about the importance of building an image, help residents discuss village development, and assist in planning the construction of village gates. Service activities in Setanggor Village can be carried out well with several directions from the community to perfect the selected gate design ideas. It is hoped that in the future, service activities like this can be carried out again in Setanggor Village to help the community in planning and developing a cultural tourism village.